Electron mobility study of hot-wall CVD GaN and InN nanowires - Cimpoiasu,Elena (2006)
A review of the dependence of the electron mobility on the free carrier concentration for gallium nitride and indium nitride nanowires grown using hot-wall chemical vapour deposition is presented. Gallium nitride nanowires exhibit mobilities of 100 cm²/Vs to below 1 cm²/Vs for carrier concentrations of 10(19) to 10(20) cm- 3. Theoretical estimations and annealing experiments indicate that the nanowires are heavily compensated. Indium nitride nanowires also exhibit high carrier concentrations, of the order of 10(20) to 10(22) cm- 3. For both types of nanowires, mobility decreases with increasing carrier concentration, consistent with transport limited by impurity scattering.